Knowledge Accessibility and the Marketing Mix Service of Thai Traditional and Alternative Medicine that - Anankabundit, Karnmanee (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed 1) to study the differences in demographic factors affecting service quality of public hospitals in Nonthaburi province, 2) to study knowledge of Thai traditional and alternative medicine related to service quality of public hospitals in Nonthaburi province, 3) to study the factors of accessibility relevant to service quality of public hospitals in Nonthaburi province, and 4) to study the factors of marketing mix service related to service quality of public hospitals in Nonthaburi province. The samples used in the research are the 400 customers of Thai traditional and alternative medicine clinics at public hospitals in Nonthaburi province. The data were collected by using a questionnaire as a tool. The statistics used in the data analysis were descriptive statistics consisting of frequency, percentage, mean, standard deviation, t-test, One-way ANOVA and Regression. The results revealed that 1) the demographics have different levels of overall service quality, while the gender aspect was not different. 2) The knowledge of Thai traditional and Chinese medicine affected service quality. 3) The accessibility affected service quality 4) Marketing mix factors such as product, price, promotion, people, physical evidence and process had effects on service quality with statistical significance at the level of .05.